Daya Saing Usahatani Jagung Hibrida di Kabupaten Lampung Selatan - Agus Imron (Politeknik Negeri Lampung, 2010)
The demands for corn in Indonesia lately increase significantly (10-15% per year) as a result of developing corn based industries. Meanwhile, domestic corn production develops relatively slow (2, 43% per year). As the result, the number of corn import increases every year. This condition can threat corn farming in Indonesia. This research is intended to analyze 1) competitiveness of hybrid corn farming in South Lampung regency, 2) response of competitiveness of hybrid corn farming towards changes of input and output prices. The data of the research were collected through survey, in which the respondents were selected with Simple Random sampling method. The data obtained then were analyzed through PAM (Policy Analysis Matrix) to determine the competitiveness of hybrid corn in South Lampung. The research showed that the hybrid corn farming in South Lampung has high comparative and competitive values. The Private Cost Value (PCR) and Domestic Resource Cost (DRC) were 0, 3590 and 0, 1157. With the PCR and DRC values were less than 1, hybrid corn farming possesses high competitiveness and therefore prospective to develop. Based on the sensitivity value, the superiority of competitive and comparative value of hybrid corn in South Lampung is sensitive to output price change and total production cost either in private or social prices. Keywords: competitiveness, comparative value, input and output prices.